Adolescent’s strategies and reverse influence in family food decision making - Othman, Mohhidin; Boo, Huey Chern; Wan Ismail, Wan Rusni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The role of adolescents in family decision making related to food consumption in Malaysia has received comparatively little or no attention by researchers although there were evidences of differences in influences found in other countries. This study addressed the research gap by testing adolescents’ bilateral strategies in influencing their family decision using family power theory. A survey of 500 adolescents from urban area was conducted to investigate their influence based on their involvement in family consumer tasks. Key findings include strong relationship between perception of influence and rewards thus indicate the existence of strategies in adolescents influence attempt.